Publish don't perish : 100 tips that improve your ability to get published - Lussier, Robert N. (Emerald Publishing Limited : Information Age Publishing, 2010)
Today, publish or perish is hitting virtually all colleges and universities. As much as we may love to teach, without publishing we may not get a faculty position, not get tenure and promotions, and publishing often affects our salaries and ability to move to a new position. Therefore, the purpose of this book is to help you get your academic work published. Thus, anyone who is interested is getting ideas that will help them get published, and those who would like to help others publish, can benefit from this book.